Unraveling the Mystery: Next Generation Sequencing Sheds Light on Neuroblastoma Pathogenesis and Targeted Therapies - Tekincan Aktas; Deniz Kızmazoglu; Safiye Aktas; Aylin Erol; Efe Serinan; Ozde Gokbayrak; Sefayi Merve Ozdemir; Zekiye Altun; Erdener Ozer; Emre Cecen; Dilek Ince; Nur Olgun (Frontiers in Bioscience-Landmark, 2023)
Background: There is considerable interest in the molecular evaluation of solid tumors in pediatric cases. Although clinical trials are in progress for targeted therapies against neuroblastoma (NB), novel therapeutic strategies are needed for high-risk cases that are resistant to therapy. The aim of the present study was to document the specific gene mutations related to targeted therapy in relapsed or refractory NB patients by using next generation sequencing (NGS). Methods: The study included 57 NB patients from amongst 1965 neuroblastic cases in Turkey who experienced a recurrence after multi-model therapy. The cases were diagnosed, risk-stratified, and treated according to the classification system from the International Neuroblastoma Risk Group. Single nucleotide variations in 60 genes were investigated using the Pillar Onco/Reveal Multicancer v4 panel and Pillar RNA fusion panel on the Illumina Miniseq platform. Results: ERBB2 I655V was the most frequent mutation and was found in 39.65% of cases. Anaplastic Lymphoma Kinase (ALK) mutations (F1174L, R1275Q, and rare mutations in the tyrosine kinase domain) were detected in 29.3% of cases. Fusion mutations in NTRK1, NTRK3, ROS1, RET, FGFR3, ALK and BRAF were observed in 19.6% of cases. Conclusions: This study presents valuable mutation data for relapsed and refractory NB patients. The high frequency of the ERBB2 I655V mutation may allow further exploration of this mutation as a potential therapeutic target. Rare BRAF mutations may also provide opportunities for targeted therapy. The role of ABL1 mutations in NB should also be explored further.